Utilization of Technology in the Teaching and Learning Process to Improve Student Learning Outcomes - Ibnu Sina; Marvel Maloti Putra Budianto; Suparmi (Aslim: Journal of Education and Islamic Studies, 2024)
The utilization of technology in education plays a crucial role in enhancing the quality of teaching in the digital era. This article discusses various strategies that can be applied to integrate technology into the learning process, such as the use of digital media (videos and e-books) and online learning platforms like learning management systems (LMS). Technology not only makes learning materials more engaging but also facilitates interaction between teachers and students through online discussions and interactive assessments. Additionally, adaptive learning applications available in LMS and data analytics can help tailor the learning experience to meet the individual needs of each student. Teacher professional development through online training and participation in educational communities is also essential for enhancing teaching skills. With the effective use of technology, more efficient and effective learning can be achieved, provided that it is supported by appropriate teaching strategies. Teachers need to have the ability to design and implement lessons effectively to meet the established goals. Therefore, it is crucial for teachers to understand various teaching strategies and to master the teaching media being used.